Magnetic nanocarriers: Evolution of spinel ferrites for medical applications - Amiri, Mahnaz; Salavati-Niasari, Masoud; Akbari, Ahmad (Advances in colloid and interface science, 2019)
A valuable site-directed application in the field of nanomedicine is targeted drug delivery using magnetic metal oxide nanoparticles by applying an external magnetic field at the target tissue. The magnetic property of these structures allows controlling the orientation and location of particles by changing the direction of the applied external magnetic field. Pharmaceutical design and research in the field of nanotechnology offer novel solutions for diagnosis and therapies. This review summarizes magnetic nanoparticles and magnetic spinel ferritʼs properties, remarkable approaches in magnetic liposomes, magnetic polymeric nanoparticles, MRI, hyperthermia and especially magnetic drug delivery systems, which have recently developed in the field of magnetic nanoparticles and their medicinal applications. Here, we discuss spinel ferrite (SF) as magnetic materials that are a significant class of composite metal oxides. They contain ferric ions and have the general structural formula M2+Fe23+O4 (where M = Co,Ni,Zn,etc.). This structure indicates unique multifunctional properties, such as excellent magnetic characteristics, high specific surface area, surface active sites, high chemical stability, tuneable shape and size, and options for functionalization. The review assesses the current efforts on synthesis, properties and medical application of magnetic spinel ferrites nanoparticles based on cobalt, nickel and zinc. Based on this review, it can be concluded that MNPs and SFNPs have unlimited ability in biomedical applications. However, the practical application of SFNPs on a huge scale still needs to be considered and evaluated. [Display omitted] •We introduced spinel ferrites as a promising carrier for biomedical applications.•Drug targeting using nanomagnetic directed at the target tissue by means of an external magnetic.•Impact of static and dynamic magnetic fields on biological systems are briefly reviewed.•Co, Ni and Zn SFNPs characterization and applications are addressed separately.•Toxicity of NPs and some parameters that must be addressed for biomedical applications.